Functional Properties of Herbal Kombucha Fermented from 4 Medicinal Plants (Ventilago denticulata Willd, Salacia chinensis L., Diospyros variegata Kurz. and Ventilago calyculata Tul.) - Khamweera, Pemika; Maisont, Suchada; Sangsirimongkolying, Ratsamee; Suchaiya, Voravadee; Chokboribal, Jaroenporn; Thonglem, Sutatip (Journal of Food Technology, Siam University, 2026)
This research aimed to utilize four local herbs: Rang Daeng (Ventilago denticulata Willd), Kamphaeng Chet Chan (Salacia chinensis L.), Phaya Rak Dam (Diospyros variegata Kurz.), and Thao Wan Lek (Ventilago calyculata Tul.), to study the functional properties of their herbal kombucha brews. The study found that all four herbal kombucha variants, produced from a 37% (w/v) herbal tea concentrate, successfully exhibited functional properties. Specifically, the highest antioxidant activity was observed in the Rang Daeng kombucha (615.54 ± 0.021 µg/mL), while the highest total phenolic content was found in the Thao Wan Lek kombucha (2.01 ± 0.059 µg/mL). The acetic acid content across all four herbal kombucha types ranged from 0.451 ± 0.0005 to 0.625 ± 0.0036 mg. Regarding flavonoid content, the Phaya Rak Dam kombucha exhibited the highest value (1.149 ± 0.039 mg/g), and the Kamphaeng Chet Chan kombucha had the lowest value (0.077 ± 0.004 mg/g). On the 7th day of fermentation, the maximum total alcohol content reached 2.95% ABV. Furthermore, during the day 7 fermentation period, the total dissolved solids, including inorganic and organic substances, ranged from 170.00 to 212.50 g/L. The total microbial count, acetic acid bacteria count, and yeast count met the standards for food products (6 log CFU/mL). Finally, no reducing sugars or natural sugars such as glucose, fructose, and sucrose were detected in g/100 mL, which falls within the acceptable criteria for healthy fermented beverages.